Lincoln Mediated - Borchard, Gregory A., author.
1 online resource (xxii, 226 pages)
Keywords: "Lincoln Mediated provides new information about a historical figure everyone thinks they know. It describes how Abraham Lincoln worked with the press throughout his political career, beginning with his service in Congress in the late 1840s, and detailing how his ties to newspapers in Illinois, New York, and Washington played a central role in the success of his presidency. Gregory A. Borchard and David W. Bulla study how Lincoln used the press to deliver his written and spoken messages, how editors reacted to the president, and how Lincoln responded to their criticism. Reviewing his public persona through the lens of international media and visually based sources, a fascinating profile emerges.The authors cite the papers of Lincoln, the letters of influential figures, and content from leading newspapers. The book also features nineteenth-century illustrations and photographs. Lincoln Mediated ties the president's story directly to the press, illuminating his role as a writer and as a participant in making the news. Lincoln's legacy cannot be understood without understanding the role the press played in helping shape how he was viewed. As the authors show, Lincoln was a man, not just a political figure. Lincoln Mediated is a worthy addition to Transaction's Journalism series."--Provided by publisher.